The third revolution Xi Jinping and the new Chinese state - Economy, Elizabeth C. (New York Oxford University Press, 2018)
This is essential reading for anyone interested in both China under Xi and how America and the world should deal with this vast nation in the coming years. "--
Includes bibliographical references and index.
Keywords: Xi, Jinping; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / Diplomacy; POLITICAL SCIENCE / Government / International; China -- Politics and government